Position and Chance of Indonesia Family Planing to Achieve RPJMN 2015-2019 and FP2020 Targets - Pinandari, Anggriyani Wahyu; Wilopo, Siswanto Agus (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Indonesia’s commitment at London Summit 2012 was to reduce TFR by increasing contraceptive users by 2020. This paper aimed to estimate the number, trend and possibility to achieve RPJMN and FP2020 targets in Indonesia. This was a descriptive study using secondary data from Indonesia national survey. Data are presented in line, bar, and pie graphs, also table to explain trend and possibility of Indonesia FP to achieve 2020 targets. Using 2012 data as the baseline, RPJMN and FP2020 targets will be achieved if CPR grows 0.5 point/year. However, recent growth was insufficient, only 0.3 additional points. The current CPR is behind the target and 1 point/year growth rate is needed to approximate the target trajectory. Based on three surveys in 2015 (PMA, SUSENAS and SUPAS), Indonesia’s CPR was predicted to be 61.1% on 2020. This is five points lower than the 2020 target, 66.3%. This discrepancy shows that Indonesia would not achieve FP target on RPJMN 2015-2019. Based on recent survey in 2015, CPR trajectory is predicted to be 5 points below the target. 1.5 points annual growth is needed to achieve the 2020 goals.